An analysis of the thesis and special problems written by Thai U.P. Education students (1963-1973) - Klomchum, Rutra 1934- (1974)
This study describes Thai thesis/special problem writers of 62 research studies undertaken for the Master of Education (M. Ed.) and Master of Arts (Education) degrees in 1963-1973. The number of Thai graduates increased every year, with the highest number graduating in 1972 (16) and the least number graduating in 1970 (2). The average Thai researcher is 30.26 years old, single, a Buddhist, and an M. Ed. graduate with major in school administration and supervision.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Dissertations, Academic -- Philippines; Thai students in the Philippines